Role of antioxidants supplementation in the treatment of atopic dermatitis: a critical narrative review - De Simoni, Edoardo; Candelora, Matteo; Belleggia, Sara; Rizzetto, Giulio; Molinelli, Elisa; Capodaglio, Irene; Ferretti, Gianna; Bacchetti, Tiziana; Offidani, Annamaria; Simonetti, Oriana (Frontiers in Nutrition, 2024)
Atopic dermatitis (AD) is a chronic inflammatory skin disease characterized by itching, epidermal barrier dysfunction, and an unbalanced inflammatory reaction. AD pathophysiology involves a dysregulated immune response driven by T helper-2 cells. Many factors, including reactive oxygen species (ROS), are involved in AD pathogenesis by causing cellular damage and inflammation resulting in skin barrier dysfunction. This narrative review aims to provide a comprehensive overview of the role of natural molecules and antioxidant compounds, highlighting their potential therapeutic value in AD prevention and management. They include vitamin D, vitamin E, pyridoxine, Vitamin C, carotenoids, and melatonin. Some studies report a statistically significant association between antioxidant levels and improvement in AD, however, there are conflicting results in which antioxidant supplementation, especially Vitamin D, did not result in improvement in AD. Therefore, the clinical efficacy of these dietary nutritional factors in the treatment of AD needs to be further evaluated in clinical trials. Meanwhile, antioxidants can be incorporated into the management of AD patients in a personalized manner, tailored to the severity of the disease, comorbidities, and individual needs.